Identification of antibiotic and antiproliferative compounds in natural orange blossom water. Issue 2 (3rd March 2016) - Roger, Benoit; Burger, Pauline; Baret, Pascal; Chahboun, Jamal; Cerantola, Stéphane; Fernandez, Xavier; Jeannot, Valérie
Abstract: Orange blossom water ( Citrus aurantium L. ssp aurantium ) is a hydrosol widely used in cosmetics, medicine and in the food industry. When exposed to sunlight for a few days, the hydrosol turns orange and a precipitate appears afterwards. Despite the economic importance of the orange blossom water, this phenomenon has never been studied and the chemical changes taking place have never been elucidated. This study reports on the comparative analysis of sunlight exposed and non-exposed hydrosols by UV-Visible spectroscopy, GC and HPLC. The formation of several indole derivatives (isatin, oxindole, indole-3-carboxaldehyde, 3, 3'-diindolylmethane, turbomycin A) induced by the exposition of orange blossom water to sunlight was observed. Two of these derivatives have already been identified as biologically active compounds: 3, 3'-diindolylmethane displays an antiproliferative activity against various human cancer cell lines and turbomycin A presents a broad-range antibiotic activity. The later one was identified in this study as the compound responsible for the orange coloration of sunlight-exposed orange blossom water.